Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/am404485t
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Regioisomers of Fullerene-Bisadducts by Tether-Directed Remote Functionalization: Investigation of Electronically and Sterically Isomeric Effects on Bulk-Heterojunction Solar Cells

Abstract: C60 bis-adduct containing a mixture of regio-isomers with different LUMO energy levels and steric geometries could greatly affect the morphological and bulk properties. To investigate the regio-isomer effect on solar cell performance, we have successfully designed and synthesized a regio-selective 4-acetatephenyl-4'-methylphenylmethano C60 bis-adduct (S-APM-CBA) by "tether-directed remote functionalization" strategy and a random 4-acetatephenyl-4'-methylphenylmethano C60 bis-adduct denoted as R-APM-CBA by trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…With the observations in this study, it can be argued that the success of IC 70 BA (and in extension, IC 60 BA) as the electron acceptor component in BHJ solar cells is serendipitous and surprising given the large number of chemical structures involved. It is noteworthy that there have been several studies on reducing the number of isomers in fullerene bisadduct materials using synthetic strategies and about the successful application in solar cell devices [ 18 22 ]. While high material purity and composition is generally considered an advantage for organic electronic materials, the material criteria for bulk heterojunction organic solar cell applications is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…With the observations in this study, it can be argued that the success of IC 70 BA (and in extension, IC 60 BA) as the electron acceptor component in BHJ solar cells is serendipitous and surprising given the large number of chemical structures involved. It is noteworthy that there have been several studies on reducing the number of isomers in fullerene bisadduct materials using synthetic strategies and about the successful application in solar cell devices [ 18 22 ]. While high material purity and composition is generally considered an advantage for organic electronic materials, the material criteria for bulk heterojunction organic solar cell applications is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence that PAFs are based on [5,6]‐open azafulleroid repeat units can be found on closer inspection of the UV–visible curves. Notably, the characteristic absorption for [6,6]‐closed fullerene derivatives at 420 nm is not observed, whereas the shoulder at ca 416 nm, characteristic of an open fulleroid structure, is seen (detailed in Table ). Therefore this isomer is the most likely for the repeat units in the polymer chain, and has been used for Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…However, SACAP results in a regio‐irregular polymer with a mixture of trans ‐3 and trans ‐2 in‐chain isomers. These intra‐chain variations can result in different C 60 lowest unoccupied molecular orbitals (LUMOs) along the chain, which may result in electronic traps . Therefore a challenge is to find a facile polymerization of C 60 that results in regio‐regular polymers.…”
Section: Introductionmentioning
confidence: 99%
“…PCEs up to 10.6% have been achieved using isomeric mixtures of fullerene bis ‐adducts, such as indene‐C 61 ‐ bis ‐adducts (IC 61 BA) in a solution processed tandem solar cell . Although not all isomerically pure bis ‐regioisomers have been tested in solar cell devices, most of the reported cases have demonstrated that pure regioisomers many times perform better than the corresponding isomeric mixtures, although some exceptions have also been noted . These observations justify the necessity to synthesize pure bis ‐adducts, and this in turn has led to a renaissance of the methods and reagents available to decrease the number of fullerene multiadduct derivative isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent activity in this area has resulted in new and regioisomerically pure bis ‐adducts that have performed reasonably well in OPV devices . In some cases, even when using the tether‐directed method, the number of isomers obtained is still rather large, for example, in the case of the synthesis of tethered bis ‐PC 61 BM (phenyl butyric acid methyl ester‐C 61 ) and tethered bis ‐DPM‐C 60 (diphenyl methano) for which the number of isomers obtained was 7 and 12, respectively. The main reasons for these observations are the lack of symmetry of the addend, in which case diastereomers can also be observed and the extreme flexibility of the tether used .…”
Section: Introductionmentioning
confidence: 99%